A highly selective synthesis of new alkenylsilsesquioxanes by hydrosilylation of alkynes. Issue 1 (30th November 2016) - Franczyk, A.; Stefanowska, K.; Dutkiewicz, M.; Frąckowiak, D.; Marciniec, B.
Abstract : In this study a selective synthesis of a series of new di- and trisubstituted ethenes with a POSS moiety was performed. Abstract : Hydrosilylation of a wide group of mono- and disubstituted (symmetrical and nonsymmetrical) alkynes with 1-dimethylsiloxy-3, 5, 7, 9, 11, 13, 15-heptaisobutylpentacyclo-[9.5.1.1 3, 9 .1 5, 15 .1 7, 13 ]octasiloxane ((HSiMe2 O)( i -Bu)7 Si8 O12, 1 ) in the presence of Karstedt's catalyst (Pt2 (dvs)3 ) has been performed for the first time. A series of new 1, 2-( E )-disubstituted and 1, 1, 2-( E )-trisubstituted ethenes with a silsesquioxane moiety were selectively afforded and fully characterized. On the basis of nuclear magnetic resonance (NMR) and infrared spectroscopy ( in situ FT-IR and/or FT-IR), the influence of alkyne structure and reaction conditions on the stereoselectivity as well as on the progress of triple bond hydrosilylation catalyzed by Pt2 (dvs)3 was explained. The results of the studies clearly indicated for which reagents the developed procedures lead to alkenylsilsesquioxanes with almost stoichiometric yields in short time, and for which other catalytic systems or methods should be considered.